(untitled) (World Bulletin of Management and Law, 2022)
This article deals with the problems of kinship relations as the main problem of public service. As the basis of the anti-corruption system for the new Uzbekistan, it is very important to study the problems of the mechanism of regulating kinship relations in the civil service system. The success of economic, social, legal and political changes in our country largely depends on solving this problem. One of the ways to improve the activity of the public administration system is to create an effective mechanism for regulating the conflict of interests and kinship relations, which will put a legal obstacle to the use of the position of the civil servants for their personal interests. The normative legal documents, norms and rules of foreign countries in this field have been thoroughly analyzed. Proposals for the prevention of consanguinity have been developed